(untitled) (Ticontre. Theory Text Translation, 2021)
Pavese defined his literary production as the process of clarification of the myth, which he tried to accomplish obstinately in all his works (the so-called «fragments of the monolith»). For him, the myth coincided with the archetypical image of the hill, the dwelling place of the irrational whose blood and sacrifice are manifestations (Paesi tuoi, La casa in collina, La luna e i falò). The exceptions to this are two novels: La spiaggia (1942), which «is not fragment of the monolith», and Il compagno (1947), «a political Bildung roman about the rise of a communist political conscience». What makes them different from the rest of Pavese’s work is that they miss the mythological element: in both of these novels, hills are almost completely missing. With my essay, I would like to show how this missing element deprive the novels of a full aesthetical completeness, forcing Pavese to rely on social elements (the description of a bourgeois environment and the awareness of an antifascist conscience). When Pavese gives up his intent of clarification of the myth, his writing lacks autonomy.